TUGAS DAN WEWENANG DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DALAM PELAKSANAAN FUNGSI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PROVINSI JAWA TENGAH PERIODE 2009 -2011 - Hasan, Amiek Soemarmi, Indarja (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Law Number 32 Year 2004 Article 42 paragraph (1) of Local Government, confirmed that the Council has the duty and authority to discuss and approve the draft law on budget in conjunction with the Regional Head. It is included in one of the functions of the Council are set out in the budget function Act No. 32 of 2004 Section 41. Such provisions also apply to the Central Java Provincial Parliament. This research was conducted in the Central Java Provincial Parliament in order to determine the duties and authority of legislatures in the budget to carry out the functions of the local budget (Budgets) and Central Java province to find out the problems faced in carrying out the functions of Council budget for the Central Java provincial budget as well as efforts to overcome these problems. Data collection method used is the study of legislation, books, papers, and other referansi related problems, namely data collection and interviews by asking questions verbally guided by the principle of non-respondents, namely leadership of Parliament and Secretary of the Central Java Provincial Parliament Povinsi Central Java. Analysis of the data from this study will be analyzed by descriptive qualitative analysis is based on the potential validity or quality data kaitanya closely with the object of research. Based on these results, the authors concluded that the duties and functions of the authority of Parliament in the implementation of the budget to the local budget (budget) of Central Java Province Period 2009-2011 is very big and important as the Central Java Provincial Parliament in carrying out the functions of the budget to budget not only limited work together with the local government in preparing budget then menetapkanya, but also to supervise the implementation of the budget, so without the intervention of Parliament in the budget of the budget function invalid and unenforceable because it means there is no executive agreement with the legislature. Hindrances faced by the legislature in the budget to carry out the functions of the local budget (budget) of the province of Central Java is the Period 2009-2011: Plans for Local Government Unit Budget less innovative and less well delivered, time sometimes delayed discussion of of schedule because the mechanism does not meet quorum, the incompatibility of local fiscal capacity, Increased Expenditure, exceptional circumstances / emergency financing policy. The Parliament attempts to resolve the problem are: Appealing Local Government Unit (SKPD), suspended the meeting to be continued the following day without closing tightly so quorum mechanism to streamline budgets are met and if possible, then made changes to the budget.